Intermetallic compound formation between Sn–3.5Ag solder and Ni-based metallization during liquid state reaction - He, Min (2012)
Ni and its alloys possess a lower reaction rate with Sn than Cu and Cu alloys. Ni-based under bump metallization (UBM) therefore receives considerable attention from the microelectronic packaging industry for the popular flipchip applications. In this work, we study the interfacial reaction of electroless Ni–P (EN) alloy and Ni UBMs with Sn–3.5Ag solder. Morphology and growth kinetics of the formed Ni3Sn4 intermetallic compound (IMC) in both systems are investigated under different reflow durations. With the Ni–P alloy as the UBM, needle-type, boomerang-type and chunk-type IMC grains coexist at short reflow time, but only chunk-type grains remain after prolonged reflow. With pure Ni as UBM, only scallop grains with faceted surfaces are found under both short and long reflow durations. The thickness of the intermetallic compound in both UBM systems is measured under different reflow conditions, from which the growth kinetics parameters are obtained. It is found that the IMC growth rate is higher with the Ni–P UBM than with pure Ni UBM. Another difference between the two UBMs is the existence of Kirkendall voids at the interface: the voids are found inside the Ni3P layer in the Ni–P UBM system after long-time reflow. However, such voids are not observed in the pure Ni UBM system.